Regional integration : the impact of cross-border cooperation and intergovernmental relations on micro-, small and medium enterprises in Southern Africa - Nkhoma, Kisa (Stellenbosch : Stellenbosch University, 2024)
Thesis (MPA)--Stellenbosch University, 2024.